GENDER DIFFERENCES IN PERCEIVING THE VALUES OF GOOD AND EFFECTIVE ENGLISH TEACHER - Ratnasari, Diana; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Universitas Suryakancana, 2024)
This study aims to investigate how female and male students view the meaning of a good and effective English teacher and use descriptive qualitative as design for this study. The study was conducted in SMP Negeri 1 Gerokgak with three class representatives, which consist of 120 students. The data were collected through open ended questionnaire by providing 10 statements regarding the characteristics of good English teacher and 10 statements for effective English teachers. The final data collected were 83 valid data with 43 female students and 40 male students from 102 questionnaire that already filled in by the students. Female students were more reliant on emotional perception in deciding on the values that constitutes a good teacher, focusing on empathy, understanding, and sensitivity. However male students seem more realistic about being a good teacher. Male students need teacher who knows their competency level. Both genders believe that a flexible and adaptable approach is essential for an effective English teacher, as they can adapt to unexpected challenges and ensure a successful learning process for both male and female students